Identification Methods of Tumor Tissue Origin Based on Different STR Typing Kits - WU Li-ming; CHEN An-qi; ZHANG Su-hua; LI Cheng-tao (Fayixue Zazhi)
ObjectiveTo establish the identification method of tumor tissue origin based on commonly used STR typing kits.MethodsForenSeqTM DNA Signature Prep kit was used to detect the typing of 27 autosomal STR loci in 55 paired tumor tissue samples （tumor tissue paired with normal tissue of the same individual） and 75 unrelated individual whole blood samples. The genotyping data of full sibling pairs and parent-child pairs of 55 tumor tissues were simulated. The number of total identical alleles （An） and identity by state （IBS） scores were calculated within the paired carcinoma （PC）, the tumor-unrelated individual （UI）, the tumor-simulated full sibling （FS） and the tumor-simulated parent-offspring （PO） groups. The tumor tissue origin identification and prediction models of 8 commonly used STR typing kits were established based on the statistical results obtained above, and an attempt was made to establish a specific model for tumor tissue origin identification. The accuracy, sensitivity and specificity were verified and evaluated using the additional 23 paired tumor tissue samples.Results（1） In any kit, there was no statistically significant difference in the number of loci shared with 0 identical allele （A0） between the PC and PO groups. The number of loci shared with 1 identical allele （A1）, 2 identical alleles （A2）, and IBS scores were statistically significant different between the PC group and the UI, FS and PO groups. （2） The An and IBS scores of different STRs varied in different groups. The A2 levels of 13 STRs （CSF1PO, D12S391, D19S433, D20S482, D2S1338, D3S1358, D4S2408, D7S820, D8S1179, FGA, TH01, TPOX, vWA） in PC group were higher than those of other STR loci. The A2 levels of two STRs （D6S1043, Penta E） in UI group were significantly lower than those of other STR loci. （3） The tumor tissue origin identification and prediction models of 8 commonly used STR typing kits and the identification model of tumor tissue origin with 15 STR loci （15-STRs） were successfully established, with sensitivity of 100%, specificity of 97.56%-99.88%, and accuracy of 97.59%-99.89%. Among them, the 15-STRs model had 100% sensitivity, 99.88% specificity, and 99.89% accuracy, which were higher than those of commonly used commercial kits.ConclusionThis study successfully establishes the tumor tissue origin identification methods with 8 commonly used STR typing kits, which expands the application of tumor tissue origin identification. In addition, the differences of different loci in the identification of tumor tissue origin were compared, and 15 STR loci which were particularly suitable for the identification of tumor tissue origin were selected, providing the data basis for the establishment of tumor origin tracing kits in future.